Canonical NF-κB promotes lung epithelial cell tumour growth by downregulating the metastasis suppressor CD82 and enhancing epithelial-to-mesenchymal cell transition - Roupakia, Eugenia; Chavdoula, Evangelia; Karpathiou, Georgia; Vatsellas, Giannis; Chatzopoulos, Dimitrios; Mela, Angeliki; Gillette, Jennifer M.; Kriegsmann, Katharina; Kriegsmann, Mark; Batistatou, Anna; Goussia, Anna; Marcu, Kenneth B.; et al. (Cancers, 2021)
Background: The development of non-small cell lung cancer (NSCLC) involves the progressive accumulation of genetic and epigenetic changes. These include somatic oncogenic KRAS and EGFR mutations and inactivating TP53 tumour suppressor mutations, leading to activation of canonical NF-κB. However, the mechanism(s) by which canonical NF-κB contributes to NSCLC is still under investigation. Methods: Human NSCLC cells were used to knock-down RelA/p65 (RelA/p65KD) and investigate its impact on cell growth, and its mechanism of action by employing RNA-seq analysis, qPCR, immunoblotting, immunohistochemistry, immunofluorescence and functional assays. Results: RelA/p65KD reduced the proliferation and tumour growth of human NSCLC cells grown in vivo as xenografts in immune-compromised mice. RNA-seq analysis identified canonical NF-κB targets mediating its tumour promoting function. RelA/p65KD resulted in the upregulation of the metastasis suppressor CD82/KAI1/TSPAN27 and downregulation of the proto-oncogene ROS1, and LGR6 involved in Wnt/β-catenin signalling. Immunohistochemical and bioinformatics analysis of human NSCLC samples showed that CD82 loss correlated with malignancy. RelA/p65KD suppressed cell migration and epithelial-to-mesenchymal cell transition (EMT), mediated, in part, by CD82/KAI1, through integrin-mediated signalling involving the mitogenic ERK, Akt1 and Rac1 proteins. Conclusions: Canonical NF-κB signalling promotes NSCLC, in part, by downregulating the metastasis suppressor CD82/KAI1 which inhibits cell migration, EMT and tumour growth.